Pelatihan E-Commerce Tiktok Shop Sebagai Media Promosi dan Penjualan Pada Generasi Z Di Desa Ayumolingo - Ismail, Juniaty; Abdullah, Mei K.; Zanna, Lizatul; Ntue, Pratiwi K.; Samaun, Nurlela (Jurnal Dharma Bhakti Ekuitas, 2023)
Observations were made on generation z who want to have their own business by promoting Gorontalo's distinctive handicrafts, namely karawo, and promoting the produce of their parents, most of whom are corn and rice farmers and cattle farmers, so that people, especially in the Gorontalo regency area, can get to know handicraft, agriculture and animal husbandry products from Ayumolingo Village, Pulubala District so that training is provided in the use of e-commerce on Tiktok, promotional features on Tiktok such as live streaming and Tiktok Shop by including links to selling products. Using the concept of a training-based approach, with pre and post-test measurements, obtained results of increasing understanding and utilization of TikTok e-commerce stores as a medium of promotion and sales. The implication of this activity on generation z is that can apply the information they get to entrepreneurial lives from an early age. Keywords: E-Commerce, TikTok Shop, Promotion, Gen Z Abstrak Observasi dilakukan pada Generasi Z yang ingin memiliki usaha sendiri dengan mempromosikan kerajinan khas Gorontalo yaitu karawo dan mempromosikan hasil bumi dari orang tuanya yang kebanyakan adalah petani jagung dan padi serta peternak sapi, agar masyarakat khususnya di wilayah kabupaten Gorontalo dapat mengenal produk kerajinan, pertanian dan peternakan dari Desa Ayumolingo Kecamatan Pulubala sehingga pelatihan diberikan dalam penggunaan e-commerce di Tiktok, fitur promosi di Tiktok seperti live streaming dan Tiktok Shop dengan mencantumkan link produk jualan. Menggunakan konsep pendekatan berbasis pelatihan, dengan pengukuran pre dan post test, memeroleh hasil peningkatan pemahaman dan pemanfaatan e-commerce toko Tiktok sebagai media promosi dan penjualan. Implikasi kegiatan ini pada Generasi Z dapat mengaplikasikan informasi yang diperoleh pada kehidupan berwirausaha sejak dini. Kata kunci: E-Commerce, TikTok Shop, Promosi, Gen Z